2022
DOI: 10.3390/toxins14030174
|View full text |Cite
|
Sign up to set email alerts
|

Corepressors SsnF and RcoA Regulate Development and Aflatoxin B1 Biosynthesis in Aspergillus flavus NRRL 3357

Abstract: Aspergillus flavus is a saprophytic fungus that can be found across the entire world. It can produce aflatoxin B1 (AFB1), which threatens human health. CreA, as the central factor in carbon catabolite repression (CCR), regulates carbon catabolism and AFB1 biosynthesis in A. flavus. Additionally, SsnF-RcoA are recognized as the corepressors of CreA in CCR. In this study, ssnF and rcoA not only regulated the expressions of CCR factors and hydrolase genes, but also positively affected mycelia growth, conidia prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…[ 128 ] Recent studies have also found that in addition to CreA, SsnF, and RcoA, which are closely related to CreA in the CCR system, also affect aflatoxin production. [ 103 ] Although deletion of ssnF and rcoA had less effect on aflatoxin than deletion of creA , they still significantly reduced aflatoxin production. Compared with the wild type, the aflatoxin content of these two knockout strains was reduced by 3‐ and 7‐fold, respectively.…”
Section: Impacts Of Ccr On Aspergillus Cell Factoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 128 ] Recent studies have also found that in addition to CreA, SsnF, and RcoA, which are closely related to CreA in the CCR system, also affect aflatoxin production. [ 103 ] Although deletion of ssnF and rcoA had less effect on aflatoxin than deletion of creA , they still significantly reduced aflatoxin production. Compared with the wild type, the aflatoxin content of these two knockout strains was reduced by 3‐ and 7‐fold, respectively.…”
Section: Impacts Of Ccr On Aspergillus Cell Factoriesmentioning
confidence: 99%
“…[ 103 ] Subsequent studies have shown that SsnF and RcoA not only regulate the expression of CCR related factors and hydrolase genes, but also positively affect conidial production and mycelial growth as global regulators. [ 103 ] For instance, in the ssnF deletion strains, the expression of amylase and xylanase genes was significantly reduced, meanwhile, the expression of CCR‐related genes, such as creA , creB , creC , creD , hulA , and schA , was also lower. [ 103 ] This study also found that the deletion of rcoA gene resulted in significant up‐regulation of the creC and creB genes, and significant down‐regulation of creD .…”
Section: Mechanism Of Carbon Catabolite Repression In Aspergillusmentioning
confidence: 99%
See 3 more Smart Citations